Pengembangan Low Power System Monitoring Karbon Monoksida (CO) Menggunakan Metode State Machine - Raka Bagas Perdana; Dahnial Syauqy; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Indonesia is a developing country that citizens rely heavily by the presence of a motor vehicle. Recently many cases which killed unexpectedly in a car with parked car burning conditions, however. The use of vehicles (cars) and according to news of the gas poisoning caused by carbon monoxide (CO). The existence of this monitoring tool is expected to reduce the risk of death is often the case. To be able to differentiate the car are road conditions and stopped at the gyro sensor use in put on the handbrake of automobiles. To find out the pollutants on the vehicle using Sensor MQ-07. In making the monitoring system will be made some state such as sleep or wake state and should be able to switch state with input from users so that applied the state machine for the low power mechanism in carbon monoxide monitoring system. Due to this system will work in quite a long period of time, then the unambiguous method of low power to reduce the burden of resource use power bank. Performance low power is required so that the system can last longer because of the relatively low power used when the system is not in use. Features of low power itself one is Sleep mode power down deadly ATmega328P some functionality. Current testing being performed generates, that the current used on the system running normally is 181.02 mA whereas when the system is in a State of Sleep only has a current of 138.2 mA. So the system is successfully reducing the current use of 42 mA.